From Sale to Agency: Reconceptualizing Informal Tobacco Contracts in Islamic Commercial Jurisprudence - Shofil Widad; Suliyanto Suliyanto (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study aims to analyze bulk tobacco trading practices from the perspective of fiqh muamalah and maqasid al-shariah. Tobacco trading is a primary source of livelihood for rural farmers, yet the system is largely controlled by middlemen who dominate price determination and weighing. This condition raises concerns regarding transparency, bargaining inequality, and compliance with Islamic commercial ethics. This research employs a qualitative empirical approach. Data were collected through observation and semi-structured interviews with farmers and intermediaries and analyzed using the Miles and Huberman interactive model supported by classical and contemporary fiqh literature. The findings reveal that tobacco transactions rely on informal verbal agreements supported by long-term social trust, while intermediaries largely control price determination and quality assessment through subjective evaluation. Unilateral weight deductions and delayed price disclosure create potential elements of gharar and weaken mutual consent. Two transaction models were identified: one with prior price agreement fulfilling the requirements of bay‘, and another with delayed price determination that may be reinterpreted as wakalah bil ujrah if compensation mechanisms are transparent. This study contributes to strengthening the application of maqasid al-shariah in rural market analysis and recommends transparent pricing, standardized weighing systems, and clearer contractual structures.